Synthesis, FT-IR and DTA Studies of Mercury Complexes of Hydrazones - Sahebalzamani, Hajar; Ghammamy, Shahriare; Mehrani, Kheyrollah; Salimi, Farshid; Mohammadian Tarighi, Nayier (Asian Journal of Chemistry, 2010)
N-Benzylidene-N-(2,4-dinitrophenyl)hydrazine (L1) and dimetheyl-4-[(4-nitro-2- nitrosophenyl)hydrazonomethyl]phenylamine (L2) were used as ligands for the synthesis of mercury(II) complexes. Vibrational study in the solid state of 2,4-dinitrophenyl hydrazine derivatives and its new mercury(II) complexes was performed by elemental analysis, IR, UVvis, 13C and 1H NMR techniques. The changes observed between the spectra of the ligands and their mercury(II) complexes allowed to establish the coordination mode of the metal in complexes and the mechanism of C-H activation is discussed. Thermal properties, TG-DTA of these complexes were also studied.